Спонтанна флора ботанічного саду Львівського національного університету імені Івана Франка - Borsukevych, L.M.; Prokopiv, A.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2012)
The systematic structure of Ivan Franko Lviv National University Botanical Garden’s spontaneous and synanthropic flora is established. It is found out that level of synanthropization of botanical garden’s spontaneous flora is considerably higher, than in flora of natural regions. In particular, it is higher, than level of synanthropization of Ukraine’s flora. It is established that percentage of synanthropic floristic autochthonic element is a little more than allochthonic one. The analysis of elementary areas has shown that distribution of species coordinate with the general level of flora’s synanthropization which in general has old Mediterranean character.